2020
DOI: 10.3201/eid2605.200198
|View full text |Cite
|
Sign up to set email alerts
|

Potential Presymptomatic Transmission of SARS-CoV-2, Zhejiang Province, China, 2020

Abstract: et al. A familial cluster of pneumonia associated with the 2019 novel coronavirus indicating person-to-person transmission: a study of a family cluster. Lancet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
394
1
14

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 462 publications
(432 citation statements)
references
References 1 publication
16
394
1
14
Order By: Relevance
“…These findings are in line with those of previous studies. 8,9,[14][15][16][17] Stratified analysis in this study found a trend towards longer incubation period of less severe cases as compared with that of more severe cases. This implies that severe cases could be detected and 'removed' from the pool of transmission sources more quickly, while less severe cases would All rights reserved.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…These findings are in line with those of previous studies. 8,9,[14][15][16][17] Stratified analysis in this study found a trend towards longer incubation period of less severe cases as compared with that of more severe cases. This implies that severe cases could be detected and 'removed' from the pool of transmission sources more quickly, while less severe cases would All rights reserved.…”
Section: Discussionmentioning
confidence: 48%
“…For example, in some studies, most cases had a long or even unclear interval of exposure, making it difficult to determine the exact exposure date 3,5,13 and giving rise to error. Besides, the order of transmission (i.e., who is infector and who is infectee) in clustering cases, which is crucial to estimation of both parameters, is easy to be mistaken given the possibility of pre-symptomatic and asymptomatic transmission, [14][15][16][17] but previous studies rarely described how this issue was handled.…”
Section: Introductionmentioning
confidence: 99%
“…This result indicated that SARS-CoV-2 was transmitted in Jiangsu Province, and the second-generation transmitted cases appeared. The epidemiology of human infections with SARS-CoV-2 in Jiangsu was also found in other areas outside Hubei Province [12,13]. A few cases were confirmed whether residents or travelers to Hubei Province or close contacts.…”
Section: Discussionmentioning
confidence: 62%
“…Some reports have already demonstrated that asymptomatic infections in children occurred in family clusters. 35,37,38 Because of the high asymptomatic ratio, pediatric COVID-19 cases are usually detected by contact tracing. Unfortunately, presymptomatic or asymptomatic transmission of SARS-CoV-2 has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, presymptomatic or asymptomatic transmission of SARS-CoV-2 has been reported. 38,39 The transmission of SARS-CoV-2 via asymptomatic children is reasonable. To date, no clustering or asymptomatic transmission among children has been documented.…”
Section: Discussionmentioning
confidence: 99%